2013
DOI: 10.1017/s0263034613000529
|View full text |Cite
|
Sign up to set email alerts
|

Fast electron transport patterns in intense laser-irradiated solids diagnosed by modeling measured multi-MeV proton beams

Abstract: The measured spatial-intensity distribution of the beam of protons accelerated from the rear side of a solid target irradiated by an intense (>10 19 Wcm −2 ) laser pulse provides a diagnostic of the two-dimensional fast electron density profile at the target rear surface and thus the fast electron beam transport pattern within the target. An analytical model is developed, accounting for rear-surface fast electron sheath dynamics, ionization and projection of the resulting beam of protons. The sensitivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…To quantify the degree of filamentation within the beam, the method used by MacLellan et al [8] is employed, where the mean coefficient of variation, C M P , represents as a percentage, the radially averaged standard deviation in proton dose divided by the radially averaged dose. This measurement allows the degree of disorder in the beam to be quantified as a function of its radius, and as we find this to be quasi-constant, we take the average value of this function, C M P , to represent the degree of disorder in the beam measured at a given proton energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To quantify the degree of filamentation within the beam, the method used by MacLellan et al [8] is employed, where the mean coefficient of variation, C M P , represents as a percentage, the radially averaged standard deviation in proton dose divided by the radially averaged dose. This measurement allows the degree of disorder in the beam to be quantified as a function of its radius, and as we find this to be quasi-constant, we take the average value of this function, C M P , to represent the degree of disorder in the beam measured at a given proton energy.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive numerical modelling and experimental studies have led to a powerfully predictive 3D hybrid model showing that low temperature plasma (10-100 eV) resistivity gradients can lead to filamentation of the electron beam [5][6][7]. Using the final electron distribution at the target rear, a sheath expansion model [8] has been shown to accurately forecast the subsequently accelerated proton distribution, and this work established a precedent for using the accelerated proton beam spatial distribution as a diagnostic of fast electron transport physics within the target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the design of FI targets is strongly inluenced by experimental results and that electron transport codes are benchmarked using these results, it is important to determine to what extent low temperature effects inluence fast electron transport in solids. Through experimentally and numerically investigating electron transport in silicon and different forms of carbon, we have recently shown that the electrical resistivity of a material at temperatures as low as a few eV plays a deining role in the evolution of resistive magnetic ields (B-ields) and thus the fast electron transport physics [10][11][12]. A picosecond pulse of fast electrons (driven by a picosecond-duration laser pulse) traverses a few hundred-micron-thick target on a timescale in which the background electrons are hot, but the ions are still relatively cold and temporarily retain their lattice structure.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 5(c) and 5(f) correspond to the calculated proton beam profiles, as obtained by mapping the fast electron density maps at the target rear surface into E-field distributions and, subsequently, into an expanding proton front. The principles behind this approach are outlined in [17], and the present modeling takes account of the evolution of the electron density distribution at the target rear. The final proton beam distributions resulting from the fast electron transport simulation results are in good qualitative agreement with the experiment results in Fig.…”
mentioning
confidence: 99%